Dancing with Philoctetes Reflections on Pain and Remembrance - Akavia, Abigail (punctum books, 2023)
Abandoned by his community, doomed to a solitary existence with his voice as sole companion: can Sophocles' Philoctetes still speak to us? What do his screams have to say? Dancing with Philoctetes: Reflections on Pain and Remembrance juxtaposes a new adaptation of Sophocles' play with an essay describing the process of bringing it to life in a world on the brink of a pandemic. Akavia investigates Sophocles' nuanced portrayal of the fragility of empathy in the face of suffering, and also shares the challenges of embodying and vocalizing Sophocles' text onstage. She proposes that the pandemic and its aftermath offer a renewed perspective on Philoctetes' thematization, not just of empathy and disease, but of the longing to return: to home, to health, to what memory holds. Akavia's treatment of Philoctetes starts out from his body and voice and journeys on to loneliness, toxic masculinity, nostalgia, cancer, dreaming, parenthood, language, ballet lessons, siblings, music, and growing up. Here, scholarship and creative non-fiction combine to tell a story of reading, performing, thinking about, and living (through) tragedy.